The enabling role of dealloying in the creation of specific hierarchical porous metal structures—A review. (15th April 2018) - Song, T.; Yan, M.; Qian, M.
Highlights: A timely review based on the dealloying-enabled hierarchical porous metals. A comprehensive summary of principles for hierarchical porous metals by dealloying. We emphasise the integration of other manufacturing methods with dealloying. The outstanding performances of dealloying-enabled hierarchical porous metals. Abstract: Hierarchical porous materials exist widely in nature as a result of the survival rules of nature. Inspired by the unique properties of these native hierarchical porous materials, researchers have long endeavoured to develop hierarchical porous metal materials for specific industrial needs. This review discusses the developments to date in hierarchical porous metallic materials by focusing on dealloying-enabled hierarchical porous structures, with or without the combination of other manufacturing processes, and their distinctive properties and industrial applications. It is shown that the dealloying method opens up new avenues in the creation of functional hierarchical porous metals for a wide variety of promising applications.